Quality Service Issues: A Case Study in an Automotive Firm - Jusoh, Muhammad Shahar; Amlus, Mohammad Harith; Ismail, Mohammad Shariff; Chin, H. M.; Lee, J.W.; Abashah, Aidanazima; Ahmad, Rosmaini (Journal of Posthumanism, 2025)
This study investigates critical quality service issues within the customer service centers of ABC Automotive, focusing on three key areas: customer service response times, clarity of communication, and the effectiveness of post-service support. The research aims to understand the impact of these issues on customer satisfaction and to propose strategic improvements. Findings indicate that prolonged delays in customer service interactions, ambiguous communication regarding service status, and inadequate post-service assistance significantly detract from the overall customer experience and compromise customer loyalty. This study offers valuable insights for ABC Automotive to address these challenges and provides a framework for other service centers seeking continuous improvement in their operational practices.